Reexamining the Environmental Kuznets Curve in Selected N-11 Countries: The Role of Financial Markets, Institutional Quality, and Environmental Technology - Nareswari, Ninditya; Fazlurrahman , Hujjatullah; Sugihartanto , Mushonnifun Faiz (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
. Economic growth is crucial for emerging economies, yet the sustainability of this growth must consider its environmental impact. The Environmental Kuznets Curve (EKC) hypothesis suggests that while economic expansion initially worsens environmental degradation, it can ultimately lead to environmental improvements as income levels rise. This study reexamined the EKC hypothesis in a selection of countries from the Next Eleven (N-11) group. Using a random effects model regression, the analysis examined the effects of gross domestic products, financial market development, institutional quality, and environmental technology on CO₂ emissions. The findings supported the EKC hypothesis, indicating that economic growth initially increased environmental degradation but eventually contributed to improved environmental outcomes. Financial market development was associated with lower CO₂ emissions, suggesting that robust financial systems may promote eco-friendly investments. In contrast, environmental technology exhibited a positive effect on CO₂ emissions, potentially reflecting an early adoption stage were technology increases emissions. Institutional quality did not show a significant impact on CO₂ emissions. Several recommendations were provided balancing economic growth with environmental sustainability